-2x+60=68+-4x

Simple and best practice solution for -2x+60=68+-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+60=68+-4x equation:


Simplifying
-2x + 60 = 68 + -4x

Reorder the terms:
60 + -2x = 68 + -4x

Solving
60 + -2x = 68 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
60 + -2x + 4x = 68 + -4x + 4x

Combine like terms: -2x + 4x = 2x
60 + 2x = 68 + -4x + 4x

Combine like terms: -4x + 4x = 0
60 + 2x = 68 + 0
60 + 2x = 68

Add '-60' to each side of the equation.
60 + -60 + 2x = 68 + -60

Combine like terms: 60 + -60 = 0
0 + 2x = 68 + -60
2x = 68 + -60

Combine like terms: 68 + -60 = 8
2x = 8

Divide each side by '2'.
x = 4

Simplifying
x = 4

See similar equations:

| -5+1=-59 | | 25x^5-5x^4+115x^3-23x^2+60x-12=0 | | 2x-8=.66x | | f(6)=3*f(6-1)+8 | | -6+5x=49 | | -2x+34=106-10x | | a^3-a^2-72a=0 | | 4(2.25+-1.75x)+7x=9 | | 8q+6+7= | | X-(-28)=16 | | -5(m+-2)+2m=-5 | | x+0.6x=46 | | 15x^4-75x^2=0 | | (2r-13)-(-6r+4)=0 | | y=x-23 | | x+0.04x=2843.36 | | 8-3x=-5+24 | | -9=-a+4 | | 3(x-3)+2x=5(x-7)-44 | | 5k+4=k+13 | | 4y+X=75 | | 90=6+4x | | 2+2(3x-4)=9-4(2x+1) | | log(25)x=y | | 12y+10=10x-18 | | 6=b+11.2 | | 0=p^2+5p+2 | | -2x+49=76+-5x | | 66+7y=-4y | | 4x-8=14-4x | | 23=-z-3 | | a-8=-5.3 |

Equations solver categories